From Fright to Shine: Transformasi Penampilan Presentasi dalam Bahasa Inggris - Kurniasih, Nuning (Universitas Pahlawan Tuanku Tambusai, 2025)
Presentation skills in English are needed in various activities, including in academic activities. This community service activity (PKM) aims to guide the audience to transform from fright, anxiety, embarrassment to confidence and shine in making presentations in English. PKM activities are carried out through workshop activities and integrated in the activities of the Library and Information Science Student Association (Himaka), Faculty of Communication Sciences (Fikom) Universitas Padjadjaran (Unpad). The workshop was held at Fikom Unpad Jatinangor Campus on 25 September 2024 and was attended by 40 students. The workshop materials included the importance of presentation skills in English, some problems in English presentations, strategies to overcome obstacles in English presentations, important elements in English presentations, and examples of presentations in scientific forums such as seminars or international conferences. The evaluation on the delivery of workshop materials was carried out by dividing the audience into 5 groups to prepare and practice presentations in English. Based on the evaluation results, it can be concluded that the workshop material can be understood by the audience and the audience has tried to apply presentation techniques and strategies during practice.